Chemical and genetic control of IFNγ‐induced MHCII expression. (18th July 2018) - Wijdeven, Ruud H; van Luijn, Marvin M; Wierenga‐Wolf, Annet F; Akkermans, Jimmy J; van den Elsen, Peter J; Hintzen, Rogier Q; Neefjes, Jacques
Abstract: The cytokine interferon‐γ (IFNγ) can induce expression of MHC class II (MHCII) on many different cell types, leading to antigen presentation to CD4 + T cells and immune activation. This has also been linked to anti‐tumour immunity and graft‐versus‐host disease. The extent of MHCII upregulation by IFNγ is cell type‐dependent and under extensive control of epigenetic regulators and signalling pathways. Here, we identify novel genetic and chemical factors that control this form of MHCII expression. Loss of the oxidative stress sensor Keap1, autophagy adaptor p62/SQSTM1, ubiquitin E3‐ligase Cullin‐3 and chromatin remodeller BPTF impair IFNγ‐mediated MHCII expression. A similar phenotype is observed for arsenite, an oxidative stressor. Effects of the latter can be reversed by the inhibition of HDAC1/2, linking oxidative stress conditions to epigenetic control of MHCII expression. Furthermore, dimethyl fumarate, an antioxidant used for the treatment of several autoimmune diseases, impairs the IFNγ response by manipulating transcriptional control of MHCII. We describe novel pathways and drugs related to oxidative conditions in cells impacting on IFNγ‐mediated MHCII expression, which provide a molecular basis for the understanding of MHCII‐associated diseases. Synopsis: IFNγ‐induced expression of MHC class II molecules in non‐immune tissue is critical for inflammation and autoimmune diseases. This study identifies novel genetic and chemical factors that control MHCII expression, and potentially autoimmune diseases. Oxidative stressors affect IFNγ‐induced MHC class II expression in non‐haematopoietic tissues. A Keap1‐Cul3‐MYST1‐BPTF axis and HDAC1/2 control IFNγ‐induced MHC class II expression. These pathways are targeted by arsenite but also by autoimmune suppressing drugs such as DMF. Abstract : IFNγ‐induced expression of MHC class II molecules in non‐immune tissue is critical for inflammation and autoimmune diseases. This study identifies novel genetic and chemical factors that control MHCII expression, and potentially autoimmune diseases.